Beitrag zur Kenntnis der Orthopteren-Fauna (Saltatoria) von Montenegro (Orthoptera: Saltatoria). - Us, Pëtr A. (Contributions to Entomology = Beiträge zur Entomologie, 1968)
Until 1955 a total of 78 species of Orthoptera (Saltatoria) were known from the territory of Montenegro. My later collections increased this number to llO species when 32 species were found for the first time in this area. New habitats were established for many known species.